A Case of Severe, Prolonged, Refractory Hypophosphatemia After Zoledronic Acid Administration. (April 2016) - Clark, Sarah L.; Nystrom, Erin M.
Zoledronic acid (ZA) administration has been associated with electrolyte abnormalities, including hypocalcemia, hypomagnesemia, hypokalemia, and hypophosphatemia. We describe a case of severe, refractory hypophosphatemia in a patient who received ZA for hypercalcemia of malignancy (HCM). Little data are available that describe the incidence or degree of severity of hypophosphatemia that can occur following ZA administration. In addition, no formal recommendations exist to guide monitoring for or management of electrolyte derangements in the setting of bisphosphonate use. Our patient required daily, high-dose phosphorus replacement beginning day 4 following ZA administration. The average daily dose of phosphorus, including both intravenous and enteral administration, was highest in the first 2 weeks after ZA, averaging 77 mmol/d days 4 through 15, and does not include sources of phosphorus from the patient's nutrition support. Despite this high amount of supplementation, which was well beyond what meets normal daily requirements and the amount expected to treat "usual" hypophosphatemia, the patient did not achieve sustained normal serum phosphorus levels for over 30 days after ZA. ZA is a favorable option for treating HCM because of its longer duration of action, potent serum calcium-lowering effects, and favorable safety profile. The risk of hypophosphatemia with ZA use is reviewed.